2021
DOI: 10.1093/ornithology/ukab041
|View full text |Cite
|
Sign up to set email alerts
|

Systematics and conservation of an endemic radiation of Accipiter hawks in the Caribbean islands

Abstract: More than one-third of the bird species found in the Caribbean are endemic to a set of neighboring islands or a single island. However, we have little knowledge of the evolutionary history of the Caribbean avifauna, and the lack of phylogenetic studies limits our understanding of the extent of endemism in the region. The Sharp-shinned Hawk (Accipiter striatus) occurs widely across the Americas and includes 3 endemic Caribbean taxa: venator on Puerto Rico, striatus on Hispaniola, and fringilloides on Cuba. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…data). Recent genetic and morphological analyses suggest that this taxon should be considered a species (Catanach et al 2021). Given the rarity of the Puerto Rican Sharp-shinned Hawk and its drastic population decline due to Hurricane Maria (Gallardo and Vilella 2017), this taxon would likely be listed as critically endangered if considered a species.…”
Section: Discussionmentioning
confidence: 99%
“…data). Recent genetic and morphological analyses suggest that this taxon should be considered a species (Catanach et al 2021). Given the rarity of the Puerto Rican Sharp-shinned Hawk and its drastic population decline due to Hurricane Maria (Gallardo and Vilella 2017), this taxon would likely be listed as critically endangered if considered a species.…”
Section: Discussionmentioning
confidence: 99%
“…For our target sequences, we selected hawkspecific versions of the probes in the 5k tetrapod probe set. We used the Phyluce pipeline (Faircloth, 2016) to assemble UCEs from several high-quality hawk tissue samples, and then selected the longest representative of each UCE to serve as a target sequence for UCE assembly for other species in the study (Catanach et al, 2021). Using these targets, we then performed five iterations of BLAST queries against each shard (created by partitioning a large dataset into several smaller datasets to ease computational requirements).…”
Section: Uce Assemblymentioning
confidence: 99%
“…The taxa in greatest need of additional sampling include the Accipiter poliogaster, various monotypic eagle genera, Pseudastur, and Rupornis magnirostris. Several species within Accipitridae are not monophyletic and a detailed revision of species limits within several clades is sorely needed (e.g., Catanach et al, 2021).Divergence time estimates may also be further refined (e.g., by including more fossil calibrations, and identifying datable biogeographic splits).…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Vaźquez-Miranda et al (2017) show that subspecies of the LeConte's thrasher (Toxostoma lecontei) found in the Vizcaino Desert of Baja California, and populations to the north, are genetically distinct and qualify as units worthy of conservation status. Catanach et al (2021) provide a textbook example of how a subspecies should be tested with modern methods. They examined the status of the hawk Accipter straitus venator from Puerto Rico using ultra-conserved elements (nuclear DNA), mitochondrial DNA (mtDNA), and morphology.…”
Section: What Exactly Is a Subspecies?mentioning
confidence: 99%